Inverted U-shaped relationship between serum vitamin B12 and α-Klotho levels in US adults: a cross-sectional study - Li, Yu-shan; Gong, Xing-ji; Du, Wen-jie; Li, Yang; He, Dong-yong; Yao, Jian; Bai, Cui (Frontiers in Nutrition, 2024)
Background: Serum vitamin B12 and α-Klotho are important markers associated with aging. Limited studies have been conducted on the relationship between vitamin B12 and α-Klotho. Objectives: This study investigated the relationship between circulating α-Klotho and vitamin B12. Methods: A total of 4502 American adults with circulating vitamin B12 levels and α-Klotho levels from the National Health and Nutrition Examination Survey (2011-2014) were included. A weighted multiple linear regression model was used to evaluate the correlation between vitamin B12 and α-Klotho levels. To clarify potential nonlinearities, smoothed curve fitting and threshold effects analysis were employed. Results: A statistically significant nonlinear relationship was found between vitamin B12 levels and circulating α-Klotho levels after adjusting for potential confounders. We observed an inverted U-shaped relationship between serum vitamin B12 levels and circulating α-Klotho levels. Notably, serum vitamin B12 levels below the threshold (1020 pg/mL) exhibited a positive correlation with circulating α-Klotho levels (β = 0.14, 95% confidence interval (CI): 0.09-0.18, P < 0.0001). Conversely, serum vitamin B12 levels above the threshold (1020 pg/mL) exhibited a negative correlation with circulating α-Klotho levels (β = -0.12,95% CI: -0.17--0.06, P < 0.0001). Sensitivity analyses were performed and consistent results were obtained. Conclusions: This study demonstrated an inverted U-shaped relationship between circulating vitamin B12 and α-Klotho in American adults. The optimal concentration of serum vitamin B12 in American adults was found.